2015
DOI: 10.1371/journal.pone.0115515
|View full text |Cite
|
Sign up to set email alerts
|

Low Na, High K Diet and the Role of Aldosterone in BK-Mediated K Excretion

Abstract: A low Na, high K diet (LNaHK) is associated with a low rate of cardiovascular (CV) disease in many societies. Part of the benefit of LNaHK relies on its diuretic effects; however, the role of aldosterone (aldo) in the diuresis is not understood. LNaHK mice exhibit an increase in renal K secretion that is dependent on the large, Ca-activated K channel, (BK-α with accessory BK-β4; BK-α/β4). We hypothesized that aldo causes an osmotic diuresis by increasing BK-α/β4-mediated K secretion in LNaHK mice. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…Thus, the increase in urinary K + excretion in response to a low-salt, high-potassium diet is attenuated in mice lacking BK channels compared with wild-type mice. 25 This provides evidence that K + secretion by BK channels is affected by ENaC activity.…”
Section: Mechanisms Of K + Secretionmentioning
confidence: 76%
“…Thus, the increase in urinary K + excretion in response to a low-salt, high-potassium diet is attenuated in mice lacking BK channels compared with wild-type mice. 25 This provides evidence that K + secretion by BK channels is affected by ENaC activity.…”
Section: Mechanisms Of K + Secretionmentioning
confidence: 76%
“…Studies showed that a low Na diet increased NKCC2 phosphorylation and caused a shift from the low-affinity NKCC2A to the high-affinity NKCC2B isoform, partly mediated by the actions of Ang II on AT1 receptors 18,41 . Ang II level is greatly increased in mice on LNaHK, but not on HK 7,8,42 . These findings suggest that elevated Ang II may be responsible for the upregulated NKCC2 activity in mice on LNaHK.…”
Section: Discussionmentioning
confidence: 87%
“…This study suggests that the ROMK2 isoform in the TAL is regulated by different signaling pathways than the ROMK1 in the ASDN. Mice on LNaHK have highly elevated aldosterone and Ang II compared to CTRL 7,8,42 . Since TAL is absent of 11-β-hydroxysteroid dehydrogenase 2 (HSD11B2) 48 , aldosterone is unlikely to regulate ROMK in TAL.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations